Conlarium sichuanense sp. nov., on Ficus virens from Sichuan Province, China - Zhang, Tian; Liu, Ning-Guo; Li, Wen-Li; Liu, Jian-Kui (Phytotaxa, 2021)
A new hyphomycetous species, Conlarium sichuanense was found on dead branches of Ficus virens (Moraceae) from a terrestrial habitat in Sichuan Province, China. The new species has sporodochial colonies on natural substate, with micronematous conidiophores and muriform, brown and subglobose to irregular-shaped conidia. The phylogenetic analysis based on combined LSU, ITS and SSU sequence data showed that Conlarium sichuanense clustered together with C. aquaticum and C. thailandense and presented as a distinct lineage. A detailed, illustrated description and comparison with related Conlarium species are provided.